Word and image : analysis and response through the illustration of a specific literary text - Jackson, David John (Michaelis School of Fine Art, 2026)
The paintings and graphic works that comprise the practical component of this project are illustrations that accompany the text of Mike Nicol's novel, Horseman (published by Bloomsbury in 1994). This document explores aspects of interconnecting historical and theoretical influences that shape the making of illustrations. I have approached this with a view to developing an understanding of the function of illustration-that is the relationship between word and image-within the context of my body of wo